The Concept of Neuroscience-Based Inclusive Islamic Education for Millennial Generation: A Literature Review - Putra, Akhmad Fitriansyah Mandala; Suyadi, Suyadi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2022)
This article aims to elaborate on the concept of neuroscience-based inclusive, tolerant Islamic education for the millennial generation. This educational model is applied to create a balanced and equal relationship between various groups that are integral parts and need each other. This education is directed at building awareness that social life requires relationships that help each other and work together among diverse community members in terms of ethnicity, ethnicity, culture, and religion. Several conflicts accompanied by acts of violence occur due to the lack of public awareness of culture and religion. The method used is library research, with data sources consisting of the latest research results in journal articles, theses, dissertations, and other relevant research reports. The results showed that neuroscience-based inclusive, tolerant Islamic education could be tried to be implemented as an effort to develop thinking skills, emotional maturity, and social awareness of the millennial generation.